2000
DOI: 10.1128/jb.182.19.5381-5390.2000
|View full text |Cite
|
Sign up to set email alerts
|

Gene Conservation and Loss in the mutS-rpoS Genomic Region of Pathogenic Escherichia coli

Abstract: The extent and nature of DNA polymorphism in the mutS-rpoS region of the Escherichia coli genome were assessed in 21 strains of enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC) and in 6 strains originally isolated from natural populations. The intervening region between mutS and rpoS was amplified by long-range PCR, and the resulting amplicons varied substantially in length (7.8 to 14.2 kb) among pathogenic groups. Restriction maps based on five enzymes and sequence analysis showed that str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…Consistent Recent studies revealed a pathotype-associated polymorphism in the mutS-rpoS region of the E. coli chromosome (14,21,39). PCR analysis showed that 29% of the afa-8 isolates differed from E. coli K-12 in the mutS-rpoS intergenic region.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Consistent Recent studies revealed a pathotype-associated polymorphism in the mutS-rpoS region of the E. coli chromosome (14,21,39). PCR analysis showed that 29% of the afa-8 isolates differed from E. coli K-12 in the mutS-rpoS intergenic region.…”
Section: Discussionmentioning
confidence: 82%
“…In comparison to E. coli MG1655, previous studies (14,21,39) revealed that EPEC, EHEC, and E. coli group B2 strains harbor specific DNA insertions within the mutS-rpoS intergenic region. A PCR assay was developed to determine the nature of the mutS-rpoS intergenic region of the afa-8 isolates.…”
Section: Methodsmentioning
confidence: 99%
“…If the mutations in the populations measured in Figure 7 are due to mutations in other parts of the pathway, then this elevated mutation rate cannot be attributed to mutation at the rpoS locus alone. However, the mutS-rpoS intergenic region has been demonstrated to be variable in enteric bacteria (Herbelin et al, 2000;Kotewicz et al, 2002Kotewicz et al, , 2003, which suggests a history of duplications and deletions in this region. This suggests that this elevated mutation rate may apply primarily at the rpoS locus.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of rpoS, however, variations are quite common and even occur between different E. coli strains (28,37,83). However, nlpD can occur alone in bacteria that do not possess an rpoS gene, such as Haemophilus influenzae (55).…”
Section: Promoters Contributing To Rpos Transcriptionmentioning
confidence: 99%